SIFamide Influences Feeding in the Chagas Disease Vector, Rhodnius prolixus - Ayub, Mahnoor; Hermiz, Mariam; Lange, Angela B.; Orchard, Ian (Frontiers in Neuroscience, 2020)
SIFamides are a family of highly conserved neuropeptides in arthropods, and in insects are mainly expressed in four medial neurons in the pars intercerebralis of the brain. Although SIFamide has been shown to influence sexual behavior, feeding, and sleep regulation in holometabolous insects such as Drosophila melanogaster, little is known about its role in hemimetabolous insects, including the blood-sucking bug, Rhodnius prolixus. In this study, we confirm the nucleotide sequence for R. prolixus SIFamide (Rhopr-SIFa) and find characteristic phenotypic expression of SIFamide in four cells of the pars intercerebralis in the brain. In addition to extensive SIFa projections throughout the entire central nervous system, SIFamidergic processes also enter into the corpus cardiacum, and project along the dorsal vessel, suggestive of Rhopr-SIFa acting as a neurohormone. Physiologically, Rhopr-SIFamide induces dose-dependent increases in heartbeat frequency in vitro suggesting the presence of peripheral receptors, and thereby indicating Rhopr-SIFa is released to act upon peripheral targets. We also explore the function of Rhopr-SIFa in R. prolixus, specifically in relation to feeding, since R. prolixus is a blood-gorging insect and a vector for Chagas disease. The intensity of SIFamide-like staining in the neurons in the brain is diminished two hours following feeding, and restocking of those cells is finished 24 hours later, indicating Rhopr-SIFa may be released at feeding. The results of temporal qPCR analysis were consistent with the immunohistochemical findings, showing an increase in Rhopr-SIFa transcript expression in the brain two hours after feeding. We also observed enhanced feeding (size of meal) in insects injected with Rhopr-SIFa whereas insects with RNAi-mediated knockdown of the Rhopr-SIFa transcript consumed a significantly smaller blood meal relative to controls. These data suggest that the four SIFamidergic neurons and associated arborizations may play an important function in the neuronal circuitry controlling R. prolixus feeding, with Rhopr-SIFa acting as a central and peripheral neuromodulator/neurohormone.